Contribución del personal de enfermería en el cumplimiento de la lista de verificación quirúrgica - Chiguano Peralta, Maritza Johana (2025)
Unsafe surgical procedures are one of the leading causes of death and disability in the world. That is why in 2008, the World Alliance for Patient Safety, ‘Safe Surgery Saves Lives’, established the Safe Surgery Checklist (SCSL) to be applied in order to reduce the occurrence of adverse events associated with surgical procedures. This research aims to evaluate the role of nurses in compliance with the safe surgery checklist through a systematic review of the current scientific literature in Ecuador. In terms of methodology, this research will take a qualitative, cross - sectional and descriptive approach. For the analysis of this research, documents were obtained from academic pages and university repositories with relevant information on the proposed topic, from 2019 to 2024, taking into account the inclusion and exclusion criteria. As for the results, it is found that nursing staff play an important role in compliance with the LVCS, as they are responsible for the correct completion of the LVCS, together with the medical team and the patient. Finally, it is concluded that there are limitations in filling out the LVCS. However, there is room for improvement, leading to better quality of care and patient safety.